Morphological and phylogenetic factors structure the distribution of damselfly and dragonfly species (Odonata) along an environmental gradient in Amazonian streams - Rafael Costa Bastos; Leandro Schlemmer Brasil; José Max Barbosa Oliveira-Junior; Fernando Geraldo Carvalho; Gareth D. Lennox; Jos Barlow; Leandro Juen (Ecological Indicators, 2021)
A range of factors may determine the structure of ecological communities in time and space, in particular niches, dispersal limits, and the evolutionary history of the species. In the last decades, the traditional focus of community ecology on species diversity and composition have been supplemented by approaches incorporating functional traits and phylogeny. Following this perspective, we evaluated the response pattern of adult damselflies and dragonflies (Odonata) along a gradient of environmental disturbance in Brazilian Amazonia, with the objective of identifying subgroups of species that respond in a similar manner to environmental filters. The study tested the hypothesis that the subgroups of species with similar responses to the environmental gradient are structured phylogenetically and will be morphologically more similar to one another than they are to the other species. Adult odonates were sampled in 98 Amazonian streams, 48 in the region of Santarém and Belterra and 50 in the municipality of Paragominas, both located in the Brazilian state of Pará. The study was based on an ecological niche modeling approach and statistical significance testing methods to identify groups of species. These species groups (latent classes) were then associated with their morphological characteristics (Abdomen Length and Thorax Length) and phylogenetic relationships. Four latent classes, containing 34 species, were generated for each region. The latent classes of the Odonata formed along the gradient of anthropogenic impact had effects of phylogenetic proximity and the species' morphological similarity. Therefore, species belonging to the same latent class are more morphologically similar and have greater similarities in evolutionary history. It seems likely, however, that other processes may be important for the understanding of the structuring of the latent classes, such as intra- and interspecific relationships, environmental plasticity, and the history of land use. Both morphology and phylogeny are important for understanding species' responses to environmental gradients.